ANALISIS DAMPAK REWARD TERHADAP MOTIVASI BELAJAR DALAM PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH DASAR - Mudita Wandani; Dwi Maryani Rispatiningsih; Ratna Setyaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning is a process carried out by teachers with students both individually and in groups. In elementary school there are many subjects, one of which is English. English is one of the local content in elementary schools. Motivation to learn English is very important so teachers must use varied educational methods. English is local content found in Elementary School. To increase students learning motivation, they can use many methods, one of which is giving rewards. Rewards are gifts. Gifts can be in the form of praise, snacks, signs of respect and appreciation. In this study, the rewards used were star point, snacks, and canteen vouchers. This research uses a qualitative method, namely a post-positivism method with natural conditions by placing the researcher as a small tool or instrument. The aim of the research was to ensure that by providing rewards students learning motivation would increase and their level of understanding of English would also increase. The result of the research show that giving rewards has an impact on increasing student learning motivation. Through giving rewards, students have a sense of competition with their classmates, students become active in learning and dare to express their opinions in the English learning process.